Educational Research on the Use of Virtual Reality Combined with a Practice Teaching Style in Physical Education: A Qualitative Study from the Perspective of Researchers - Daniel Bores-García; Roberto Cano-; María Espada; Nuria Romero-Parra; Diego Fernández-Vázquez; José Manuel Delfa-; Víctor Navarro-López; Domingo Palacios-Ceña (MDPI AG, 2024)
(1) Background: the scientific literature has shown that students' active involvement in the teaching-learning process significantly improves their learning outcomes. (2) Methods: this study shows the perceptions of seven researchers on the process of inquiring about the effects of the combined use of virtual reality (VR) and a practice teaching style in physical education in secondary educational institutions. (3) Results: the results obtained from the researchers' diaries and the focus group, through qualitative design, are arranged in the following categories: difficulties in data collection before, during, and after the intervention; perceived differences between VR interventions in laboratory situations and educational contexts; and the perceived transferability of the use of VR devices in the educational context. (4) Conclusions: more research is needed on the use of VR in the educational context, although the results obtained indicate that the teaching-learning process can be enriched by overcoming the difficulties inherent to the use of this technology in a variable context such as education.